2020
DOI: 10.1038/s41467-020-14424-8
|View full text |Cite
|
Sign up to set email alerts
|

Modular detergents tailor the purification and structural analysis of membrane proteins including G-protein coupled receptors

Abstract: Detergents enable the purification of membrane proteins and are indispensable reagents in structural biology. Even though a large variety of detergents have been developed in the last century, the challenge remains to identify guidelines that allow fine-tuning of detergents for individual applications in membrane protein research. Addressing this challenge, here we introduce the family of oligoglycerol detergents (OGDs). Native mass spectrometry (MS) reveals that the modular OGD architecture offers the ability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
184
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(193 citation statements)
references
References 59 publications
7
184
1
1
Order By: Relevance
“…Generally, there is no one detergent appropriate for all receptors, requiring screening to find a suitable candidate. Indeed, taking a modular approach a recent publication demonstrated that varying tail and head groups can greatly affect the functionality and lipid retention of preparations of NTR1 [ 180 ]. Within the family of alkyl glucosides, it seems that varieties with branched alky chains, in particular LMNG, increase the stability of isolated receptors [ 181 , 182 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…Generally, there is no one detergent appropriate for all receptors, requiring screening to find a suitable candidate. Indeed, taking a modular approach a recent publication demonstrated that varying tail and head groups can greatly affect the functionality and lipid retention of preparations of NTR1 [ 180 ]. Within the family of alkyl glucosides, it seems that varieties with branched alky chains, in particular LMNG, increase the stability of isolated receptors [ 181 , 182 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…The basicity of detergents has recently been identied as a key parameter for controlling charge reduction in membrane protein mass spectrometry. 7,59 This prompted an important question. Can azobenzene detergents be used for controlling protein charge reduction by light?…”
Section: Membrane Protein Charge Reductionmentioning
confidence: 99%
“…60 Detergents are in many ways important for the native MS analysis of membrane proteins as they can protect the native structure in solution and during the nESI process. 6,8,59 The detergent concentration used for solubilising membrane proteins is oen adjusted to a multiple of the detergents' critical aggregation concentration (cac). 8 Attempts to solubilise AmtB with concentrations below the cac of trans 6 led to protein precipitation, thus underlining that at least concentrations close to the cac are needed to stabilize AmtB in aqueous buffer.…”
Section: Membrane Protein Charge Reductionmentioning
confidence: 99%
“…Control of detergent concentration is also vital as too much detergent can prevent crystallisation and promotes detergent phase separation and detergent crystals. In some cases, a suitable mixture of detergents must be used to alter the protein-detergent complex instead of a single detergent which is sufficient in most cases [188].…”
Section: Membrane Protein Crystallisation and Data Collectionmentioning
confidence: 99%